(untitled) (Journal of EAHIL, 2020)
Terkko Health Hub is a startup community, a co-working area and an event space focused on health and life sciences. The Meilahti Campus Library of Helsinki University Library also operate in the Hub. A library is an important meeting place and learning environment. In the library, you will meet people and the feeling of belonging to a university community is amplified. The co-operation with Terkko Health Hub started when the library removed part of the printed collection and freed space was available for alternative use. We were satisfied and excited on the campus about the new collaboration.